1981
DOI: 10.1002/aic.690270210
|View full text |Cite
|
Sign up to set email alerts
|

Wrong‐way behavior of packed‐bed reactors: 1. The pseudo‐homogeneous model

Abstract: A sudden reduction in the feed temperature to a packed-bed reactor leads to a transient temperature rise, which is referred to as the wrong-way behavior. A pseudo-homogeneous plug-flow model is used to analyze the structure of this transient behavior. The key parameters which determine the magnitude of this response are the dimensionless adiabatic temperature rise, activation energy, heat transfer capacity, coolant temperature, magnitude of temperature drop and length of the reactor. A simple expression is der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 12 publications
2
32
2
Order By: Relevance
“…When the axial dispersion of heat is very small, the maximal transient peak temperature may be very large due to the high Peclet number for heat transfer. This is consistent with the earlier predictions by Mehta et al (1981).…”
Section: Analysis Of Wrong-way Behaviorsupporting
confidence: 94%
See 3 more Smart Citations
“…When the axial dispersion of heat is very small, the maximal transient peak temperature may be very large due to the high Peclet number for heat transfer. This is consistent with the earlier predictions by Mehta et al (1981).…”
Section: Analysis Of Wrong-way Behaviorsupporting
confidence: 94%
“…This slowly moving temperature peak may damage the catalyst or the reactor, and may initiate undesired side reactions. The slow movement of this temperature wave is a new feature not predicted by the limiting model of Mehta et al (1981) and is due to the axial heat conduction. When the new feed temperature is higher than the extinction point, a suddent reduction in the feed temperature can lead to two different behaviors.…”
Section: Multiple Steady States For Some Feed Temperaturesmentioning
confidence: 93%
See 2 more Smart Citations
“…McGreavy and Naim (1977) and Windes et al (1989) studied this subject through one and two-dimensional mathematical models. Metha, Sams and Luss (1981) found analytical criteria to predict that behavior, for zero-order reactions. Pinjala, Chen and Luss (1988) analyzed the importance of the thermal dispersion on the transient response, and concluded that the ignition of the reactor during the transient period is possible to occur.…”
Section: Introductionmentioning
confidence: 99%